The Migration Processes in Ghana: The Case of Northern Migrants - Shamsu Deen-Ziblim; Adadow Yidana (African Human Mobility Review, 2021)
Over the past four decades, Accra has witnessed an increasing influx of young women who migrate to the city with the sole aim of carrying goods. This paper examines the migration processes of these young women, who mostly migrate from the northern part of Ghana to Accra, in the South. A sample of 216 female porters were selected for the study. A survey, personal interviews, and focus group discussions were the main tools for data collection. The reasons for their migration, the parties involved in the decision to migrate, and how their migration was financed were explored. The study revealed that the migration process of female porters is enabled by social networks; the women have varying levels of social capital, which facilitates movement and settlement. These social networks increase the social asset base of female porters and provide safety nets for them. It is found that the reasons for their migration are related to the declining importance of agriculture and the non-availability of jobs at their origin, which can be blamed on the liberalisation of the Ghanaian economy. It is also found that mothers are deeply involved in their daughters’ migration decisions.